Sinergi Budaya Lokal Dan Nilai-Nilai Agama Dalam Membina Kerukunan Masyrakat Pedesaan - Sabaruddin Sabaruddin; Andi Batara Indra; Fajrul Ilmy Darussalam; Agustan Agustan (SOSIORELIGIUS, 2020)
This paper tries to examine that all religions essentially teach the importance of harmony. Islam, for example, calls on all human beings regardless of ethnicity, race, and intergroup to get to know each other. The synergy between the values of teachings in each religion with local cultural values is able to foster harmony between religious communities in Toraja. The local cultural value of the Tongkonan traditional house is Ma'tongkonan or a meeting held by the family in discussing and solving all problems, this is in line with the values taught in every religion.